Perbedaan Adversity Quotient Siswa Ditinjau dari Jenis Kelamin - Winda, Rahma; Sukmawati, Indah (Lembaga Yasin AlSys, 2025)
This research is motivated by the phenomenon of students who easily despair when facing subjects that are considered difficult and do not have the fighting power to try to complete the lesson and are pessimistic about their abilities, this is a characteristic of an individual who has a weak adversity quotient. This study aims to describe the adversity quotient of students and examine the differences in adversity quotient of male and female students. The research method used is quantitative method with comparative research type. The population in this study were students at SMPN 10 Padang, totaling 847 students. The sample in this study was 272 students selected using stratified random sampling technique. Data collection techniques using adversity quotient scale which then processed using descriptive statistical techniques and independent sample t-test techniques. The results showed that students' adversity quotient was generally in the high category (48.2%). In terms of differences in the adversity quotient of men and women, a significant value of 0.223> 0.05 is obtained, which means that there is no significant difference, which means Ho is accepted. Based on the results, it is concluded that guidance and counseling teachers can provide assistance to improve adversity quotient in the form of providing information services, group counseling services and group guidance services without considering gender differences.